2019
DOI: 10.3389/fncel.2019.00192
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Polymerization Promoting Protein, Ringmaker, and MAP1B Homolog Futsch Coordinate Microtubule Organization and Synaptic Growth

Abstract: Drosophila Ringmaker (Ringer) is homologous to the human T ubulin P olymerization P romoting P roteins (TPPPs) that are implicated in the stabilization and bundling of microtubules (MTs) that are particularly important for neurons and are also implicated in synaptic organization and plasticity. No in vivo functional data exist that have addressed the role of TPPP in synapse organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 70 publications
3
19
0
Order By: Relevance
“…In control animals, elevating Futsch levels increased both the number of Futsch loops and type Ib boutons (Fig. 3, E and F), consistent with previous reports that increasing Futsch levels and microtubule stability stimulates type Ib bouton formation (Shi et al, 2019;Roos et al, 2000;Nechipurenko and Broihier, 2012). The over-expression of Futsch in K394R mutant neurons rescued Futsch loop formation, restoring loop numbers to normal, and also suppressed the formation of extra boutons (Fig.…”
Section: Abnormal Synaptic Morphogenesis In K394r Mutant Is Caused By a Decrease In Microtubule Stabilitysupporting
confidence: 90%
“…In control animals, elevating Futsch levels increased both the number of Futsch loops and type Ib boutons (Fig. 3, E and F), consistent with previous reports that increasing Futsch levels and microtubule stability stimulates type Ib bouton formation (Shi et al, 2019;Roos et al, 2000;Nechipurenko and Broihier, 2012). The over-expression of Futsch in K394R mutant neurons rescued Futsch loop formation, restoring loop numbers to normal, and also suppressed the formation of extra boutons (Fig.…”
Section: Abnormal Synaptic Morphogenesis In K394r Mutant Is Caused By a Decrease In Microtubule Stabilitysupporting
confidence: 90%
“…The seven polymorphisms with the lowest loglikelihoods in the short sleeper replicate 1 population (i.e., the lowest 5%) include four intergenic polymorphisms. www.nature.com/scientificreports/ it regulates microtubule formation necessary for proper organization and growth of the synapses at the larval neuromuscular junction 69 . Fkbp14 reduces Notch signaling 70 , which in turn can affect the response to sleep loss 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead it was observed that new boutons emerge from the presynaptic arbor by budding off round varicosities of membrane 27 . These studies also revealed that, in addition to microtubule remodeling [28][29][30][31][32][33][34] , new bouton growth induced by elevated activity is associated with actin cytoskeleton dynamics 27,[35][36][37] and requires proteins that regulate synaptic vesiclemachinery [38][39][40] suggesting that neuronal remodeling is likely coupled to synaptic transmission. Additionally, several signaling pathways have been shown to be implicated in the causal relationship between synaptic activity and bouton formation suggesting that activity-dependent plasticity at the NMJ results from a complex sequence of factors that are involved in the communication between MNs, muscle and glial cells 25 .…”
Section: Mainmentioning
confidence: 96%